Numerical Analysis of Stable (FAPbI3)0.85(MAPbBr3)0.15-Based Perovskite Solar Cell with TiO2/ZnO Double Electron Layer - Yongjin Gan; Guixin Qiu; Binyi Qin; Xueguang Bi; Yucheng Liu; Guochao Nie; Weilian Ning; Ruizhao Yang (Nanomaterials, 2023)
Although perovskite solar cells have achieved excellent photoelectric conversion efficiencies, there are still some shortcomings, such as defects inside and at the interface as well as energy level dislocation, which may lead to non-radiative recombination and reduce stability. Therefore, in this study, a double electron transport layer (ETL) structure of FTO/TiO2/ZnO/(FAPbI3)0.85(MAPbBr3)0.15/Spiro-OMeTAD is investigated and compared with single ETL structures of FTO/TiO2/(FAPbI3)0.85(MAPbBr3)0.15/Spiro-OMeTAD and FTO/ZnO/(FAPbI3)0.85(MAPbBr3)0.15/Spiro-OMeTAD using the SCAPS-1D simulation software, with special attention paid to the defect density in the perovskite active layer, defect density at the interface between the ETL and the perovskite active layer, and temperature. Simulation results reveal that the proposed double ETL structure could effectively reduce the energy level dislocation and inhibit the non-radiative recombination. The increases in the defect density in the perovskite active layer, the defect density at the interface between the ETL and the perovskite active layer, and the temperature all facilitate carrier recombination. Compared with the single ETL structure, the double ETL structure has a higher tolerance for defect density and temperature. The simulation outcomes also confirm the possibility of preparing a stable perovskite solar cell.